Corruption and Confidence in Public Institutions : Evidence from a Global Survey - Clausen, Bianca; Kraay, Aart; Nyiri, Zsolt (World Bank, Washington, DC, 2014)
Well-functioning institutions matter for economic development. In order to operate effectively, public institutions must also inspire confidence in those they serve. The authors use data from the Gallup World Poll, a unique and very large global household survey, to document a quantitatively large and statistically significant negative correlation between corruption and confidence in public institutions. This suggests an important channel through which corruption can inhibit development by eroding confidence in public institutions. This correlation is robust to the inclusion of a large set of controls for country and respondent-level characteristics, and they show how it can plausibly be interpreted as reflecting at least in part a causal effect from corruption to confidence. The authors also show that individuals with low confidence in institutions exhibit low levels of political participation, show increased tolerance for violent means to achieve political ends, and have a greater desire to "vote with their feet" through emigration.